The Effect of Marketing Mix Strategy on Interest in Returning to Tourism Objects Sekunyit Beach, South Bengkulu Regency - Julita Netri Vurwanda; Eti Arini (Journal of Indonesian Management, 2023)
The purpose of this study was to determine the effect of product, price, location, promotion and marketing mix on the intention to return to the Sekunyit Beach tourist attraction, South Bengkulu Regency. This research is a type of quantitative research. The method used in this research is descriptive method. Data collection techniques are observation and questionnaires. Data analysis techniques used descriptive analysis, multiple regression analysis, coefficient of determination (R2) and hypothesis testing. Based on the results of research on the effect of product, price, location and promotion on the decision to visit Sekunyit Beach Tourism, the following conclusions can be drawn: There is an influence of product (X1) on interest in visiting (Y) Sekunyit Beach Tourism with a significance value of 0.001 <0 .05 and tcount > ttable (8.780> 1.66196) thus Ho is accepted and Ha is rejected. There is an effect of price (X2) on interest in visiting (Y) Sekunyit Beach Tourism with a significance value of 0.000 <0.05 and tcount > ttable (7.714>1.66196). There is an influence of location (X3) on interest in visiting (Y) Sekunyit Beach Tourism with a significance value of 0.000 <0.05 and tcount > ttable (5.320>1.66196) thus Ho is rejected and Ha is accepted. Likewise, Ho is rejected and Ha is accepted. There is an influence of promotion (X4) on interest in visiting (Y) Sekunyit Beach Tourism with a significance value of 0.001 <0.05 and t count > t table (7.714> 1.66196). Likewise, Ho is rejected and Ha is accepted. The Fsig value is 0.000 <0.05 and Fcount > Ftable (10.611 > 2.47), so it can be written that together product, price, location and promotion influence the interest in visiting Sekunyit Beach Tourism.